2020
DOI: 10.1080/00343404.2020.1817364
|View full text |Cite
|
Sign up to set email alerts
|

Smart Specialisation on the move: reflections on six years of implementation and prospects for the future

Abstract: This editorial is structured as follows. The next section provides a brief introduction to the genesis of the Smart Specialisation policy. The third section describes the content of the contributions included in the special issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 8 publications
1
17
0
6
Order By: Relevance
“…By tackling this research question, the research objective of the current article also contributes to the Blue Growth Strategy for the BSR (European Commission, 2017) and the European Green Deal of the European Commission (COM/2019/640 final) by improving the conditions for the competitiveness of small and medium-sized ports. Hence, the conducted research supports European Blue Economy in line with Regional Innovation Strategies on Smart Specialisation (RIS3), which is also seen as a crucial policy approach for the implementation of the EU Green Deal (Gianelle et al, 2020;Larosse et al, 2020). Besides research and development as well as networking, training is seen as a key enabling procedure to foster and implement the smart specialisation approach (Prause, 2014), underlining the importance of this research article and its impact on the Baltic Sea and European development.…”
Section: Introductionmentioning
confidence: 55%
“…By tackling this research question, the research objective of the current article also contributes to the Blue Growth Strategy for the BSR (European Commission, 2017) and the European Green Deal of the European Commission (COM/2019/640 final) by improving the conditions for the competitiveness of small and medium-sized ports. Hence, the conducted research supports European Blue Economy in line with Regional Innovation Strategies on Smart Specialisation (RIS3), which is also seen as a crucial policy approach for the implementation of the EU Green Deal (Gianelle et al, 2020;Larosse et al, 2020). Besides research and development as well as networking, training is seen as a key enabling procedure to foster and implement the smart specialisation approach (Prause, 2014), underlining the importance of this research article and its impact on the Baltic Sea and European development.…”
Section: Introductionmentioning
confidence: 55%
“…This is the case, among others, of Partridge, Rickman, Rose Olfert and Tan (2013), Varga (2017), Magro and Wilson (2019), Blomi and Erlich (2020). Finally, studies that analyze the particular case of the application of specific public policy instruments aimed at the implementation of place-based policies -such as the regional smart specialisation strategies -and where the work of, among others, Neto, Serrano and Santos (2018), Gianelle, Guzzo and Mieszkowski (2020), Gianelle, Kyriakou, McCann and Morgan (2020), Neto and Santos (2020), Trippl, Zukauskaite and Healy (2020), Veldhuizen (2020), is contained.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Having defined specializations was also a condition for applying for and benefiting from European funds, which forced many regions to carry out entrepreneurial discovery processes in a copycat fashion (Di Cataldo et al, 2021). These processes themselves led by the regions has been ambiguously evaluated in the literature (D'Adda et al, 2019;Gianelle et al, 2020a;2020b;Iacobucci and Guzzini, 2016), with better and worse practices found, such as too much routine in a number of underdeveloped regions, or novel approaches in southern regions (Kroll, 2015). Assessments of SS's effectiveness in inducing regional development have also been equivocal, pointing to concerns about translating theory into practice (Gianelle et al, 2020a;McCann and Ortega-Argilés, 2015; and the much longer time frame for achieving strategy goals (Klikocka, 2019).…”
Section: Introductionmentioning
confidence: 99%